Self-healing during electrical treeing: A feature of the two-phase liquid-solid nature of silicone gels - Salvatierra, Lucas Matías (2016)
We report the results of electrical treeing tests carried out on a range of silicone dielectric gel samples made by varying the ratio of the same two components used for cross-linking a commercial silicone gel. These samples range from liquids to elastomers via two-phase gels. The extent of the curing is followed by means of FTIR spectroscopy and the samples are characterized through their dynamical mechanical properties. It is shown that the gel samples exhibit treeing behavior that includes features typical of both liquids and solids. A filamentary structure is produced that has permanence together with attached bubbles that self-heal locally during treeing, although differences in detail were found depending on the degree of curing. Removal of the treeing voltage allows a more substantial self-healing to occur. This behavior is discussed in terms of the two-phase liquid-solid nature of the silicone gels.